2019
DOI: 10.1080/03043797.2019.1646709
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm lost’ – a qualitative analysis of student teams' strategies during their first experience in problem-based learning

Abstract: Future global challenges that engineering graduates face have placed demands on engineering education and how graduates develop competency in collaborative problem-solving. Such demand has seen an increase in the use of pedagogies like problem-based learning (PBL) that provide opportunities for developing collaborative problem-solving skills. PBL has been well studied however there is still much to understand about 'how' students solve problems collaboratively in PBL settings. This work investigates the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Regarding group processes, Mabley et al (2020) found that students in project groups tend to impose rigid, disciplinary structures on the group problem-solving process, thereby decreasing the depth of individual student engagement with the problem. Pihl (2015) showed that forming a group consensus around the project's design and direction can harm individual student creativity.…”
Section: Student Experiences In Pblmentioning
confidence: 99%
“…Regarding group processes, Mabley et al (2020) found that students in project groups tend to impose rigid, disciplinary structures on the group problem-solving process, thereby decreasing the depth of individual student engagement with the problem. Pihl (2015) showed that forming a group consensus around the project's design and direction can harm individual student creativity.…”
Section: Student Experiences In Pblmentioning
confidence: 99%
“…In the second case, the group does not work collaboratively on the project any longer and there is a clear divide within the group. This is a challenging situation for students and Mabley (Mabley, Ventura-Medina, and Anderson 2020) showed in their empirical study on group problem solving strategies that students have a tendency to adopt relatively rigid structures and find it often difficult to move beyond what is familiar to them. With this in mind, facilitation of group dynamics is a key element in PBL and it is important that faculty and student assistants can help students to become aware, reflect upon, and work with the underlying processes (Kolmos et al 2008).…”
Section: Student-student Relationsmentioning
confidence: 99%
“…In a PBL environment, students must have an active role during the entire learning process, from identifying and understanding the problem to proposing and evaluating potential solutions. Moreover, PBL is a didactic technique highly oriented to collaborative work (Mabley et al, 2019), to the development of competencies (Webster, 2022), and with a focus on scenarios related to real problems (Jaeger et al, 2021); thus, it has very relevant elements for the research work that is developed herein.…”
Section: Introductionmentioning
confidence: 99%